The design and manufacturing of fluidic oscillators for composite aircraft structures. (March 2019) - Aly, Ahmed; Colton, Jonathan
Active flow control devices have been proven to reduce drag and delay stall on commercial aircraft. This leads to lower fuel usage and thus reduced flight costs. However, there is a large uncertainty as to how to integrate active flow control devices into aircraft, specifically those with composite structures. In addition, the cost of manufacturing active flow control devices for large-scale production has not been previously studied. In this article, design concepts for the attachment of a fluidic oscillator to a composite aircraft structure are investigated. A systematic approach from the conceptual design to the final design is performed using different design tools. A cost analysis is performed to select the most cost-effective design configuration based on large volume fluidic oscillator production. Through design validation and cost estimation, the final design is shown to be feasible for large volume manufacturing.